Aesthetic Breast Reconstruction With De-epidermized Deep Inferior Epigastric Artery Perforator Flap and Thoracoabdominal Advancement Flap - Haïzam Oubari, MD, MSc; Fabien Boucher, MD; Abdulrahman Hashim, MD; Franck Dupuy, MD; Hristo Shipkov, MD, PhD; Ali Mojallal, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Most regard the deep inferior epigastric artery perforator (DIEP) flap as the gold standard in autologous breast reconstruction, with good breast aesthetics achieved and low donor site morbidity. Mojallal et al introduced a new surgical protocol to enhance results for both the breast and abdomen further. This study presented the first clinical series of patients benefitting from breast reconstruction based on a combination of a DIEP flap and a thoracoabdominal advancement flap (TAAF). Methods:. A retrospective study was conducted at our institution from January 2013 to October 2020. We included all 100 consecutive patients in whom the technique was used. Patients’ characteristics, types of surgical procedures, and outcomes were recorded. Patient satisfaction and quality of life were measured with BREAST-Q 2.0 reconstructive modules. Results:. A total of 101 DIEP flaps and 100 TAAFs were included. The mean follow-up was 26.9 months. In all cases, the DIEP skin paddle could be removed, and the abdominal scar was concealed under the patient’s undergarments. No TAAF necrosis or major abdominal complications were recorded. Four DIEP flap failures were successfully treated with implants, lipofilling, or muscle-sparing latissimus dorsi flaps while preserving the benefit of the TAAF. Breast and abdominal aesthetics were satisfying, with high BREAST-Q scores. Conclusions:. The TAAF combined with the DIEP flap is a reliable technique for delayed unilateral breast reconstruction. Excellent aesthetic results and high patient satisfaction can be achieved without compromising safety.